Exploring EFL teacher resilience in the Chinese context. (April 2022) - Liu, Honggang; Chu, Wenxiu
Abstract: Teacher resilience (TR) has been widely researched in recent years in the general education field. However, scant attention has been given to language teacher resilience (LTR). An in-depth and systematic exploration of the inner structure of LTR is still lacking, which somewhat hinders our understanding of LTR. To address this gap, this study adopted a quantitative approach to investigate the structure of resilience among teachers of English as a foreign language (EFL). An adapted Chinese version of the Connor–Davidson Resilience Scale (CD-RISC) (Connor & Davidson, 2003) was completed by 658 Chinese senior high school EFL teachers. Exploratory and confirmatory factor analyses found a tri-factorial structure of TR involving tenacity, optimism and coping style; the latter was a newly discovered component of TR. In addition, we examined levels of EFL TR and found that they remained moderate to high. On the basis of these findings, the paper offers implications for sustaining and developing EFL TR and proposes future directions for LTR research.